Desire in the Renaissance : Psychoanalysis and Literature - Finucci, Valeria (Book collections on Project MUSE., 2001)
Drawing on a variety of psychoanalytic approaches, ten critics engage in exciting discussions of the ways the "inner life" is depicted in the Renaissance and the ways it is shown to interact with the "external" social and economic spheres. Spurred by the rise of capitalism and the nuclear family, Renaissance anxieties over changes in identity emerged in the period's unconscious--or, as Freud would have it, in its literature. Hence, much of Renaissance literature represents themes that have been prominent in the discourse of psychoanalysis: mistaken identity, incest, voyeurism, mourning, and th.